Spontaneous Retroperitoneal Hemorrhage in a Patient with Prolymphocytic Transformation of Chronic Lymphocytic Leukemia. (19th August 2013) - Davies, Gwynivere A.; Lazo-Langner, Alejandro; Shkrum, Michael; Minuk, Leonard
Abstract : Prolymphocytic transformation of chronic lymphocytic leukemia is a rare but recognized entity. We present the case of a 76-year-old gentleman with a previous diagnosis of chronic lymphocytic leukemia who presented with fatigue, fever, and a white blood cell count of 500 000 with prolymphocytes on peripheral blood examination. Chlorambucil and dexamethasone were initiated. He developed progressive anemia during his admission with no clear cause on initial CT examination. Bilateral hip pain began several days later and he was unfortunately diagnosed with a large spontaneous retroperitoneal hemorrhage postmortem. This condition is rare and generally occurs in those receiving therapeutic anticoagulation or dialysis, with known bleeding disorders or vascular malformation, none of which were present in our patient. Pathology revealed marked leukemoid engorgement of the vessels of many organs with prolymphocytes. We discuss the potential etiologies and relationships between these critical diagnoses.